Parent Roles and Facilitation Strategies as Influenced by a Mobile-Based Technology During a Family Nature Hike. Issue 2 (3rd July 2018) - McClain, Lucy R.
Abstract: Families use mobile technologies in many educational spaces, such as museums or other informal learning venues to support their social learning experience. This trend encourages parents to take on new facilitation roles during their children's technologically driven learning experiences. This study provides an in-depth look at how one type of mobile technology shaped parent roles, facilitation, and family learning in an outdoor setting. The qualitative case study uses sociocultural learning theory with a lens toward parent roles during a mobile-based family learning experience in the outdoors to analyze the 1-hour hike of one case study family. Findings from a thematic analysis of the video data resulted in 6 parental roles embodied by the parents during their hike with an e-Trailguide. A secondary analysis provided evidence that the e-Trailguide facilitated collaborative observations of the natural world for the parents and children. Recommendations for mobile-based designs that support family, outdoor learning are included.